Measuring the impact of specific factors in improving the level of human development in Iraq during the period (1990-2020) (Raparin Journal of Humanities (RJH), 2024)
The subject of human development is one of the most important topics that occupies an important place in the economies of the countries of the world, which prompts the adoption of a correct and rational methodology to draw scientific conclusions and recommendations aimed at promoting and developing human development. and livelihood), and attention to these aspects constitutes an important part in the development plans of any country in order to create a strong base and a people with skilled labor, and investing in human capital has long-term positive benefits that are reflected on the individual in particular and on society in general, which shows that it is an important investment and the value of human investment. The research reached a set of conclusions, the most important of which were: that health, educational and living human development indicators suffer from further deterioration, neglect and deterioration of their actual reality during the study period, and despite the presence of an improvement in the value of the human development index for Iraq, it is not in line with the reality of human development indicators In the country, the research ends with a set of recommendations, the most prominent of which are: the need to increase financial allocations in human capital investment, improve the health of individuals and improve their standard of living.